1991
DOI: 10.1161/01.hyp.18.3.366
|View full text |Cite
|
Sign up to set email alerts
|

Zinc metallopeptidase inhibitors. A novel antihypertensive treatment.

Abstract: Inhibitors of two zinc metallopeptidases, angiotensin I converting enzyme (ACE) and neutral metalloendopeptidase-24.11 (EP-24.11), are antihypertensive agents. In this issue of Hypertension, Genden and Molineaux report that yet another peptidase inhibitor, metalloendopeptidase-24.15, EC 3.4.24.15 (EP-24.15), lowers blood pressure in normotensive rats. In this editorial we discuss the possible role of kinins as common mediators of part of the vasodepressor action of these peptidase inhibitors. Genden and Moline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The effect of improving renal function after chelation therapy might theoretically relate to removal of essential trace elements, such as zinc and copper, which act as cofactors for enzymes that affect synthesis of vasoactive hormones. 18,19 For example, zinc is a cofactor for neutral metalloendopeptidase, a kidney enzyme of degrading atrial natriuretic peptide, 26 and for angiotensin-converting enzyme. 27 A depletion of zinc might cause an elevation in atrial natriuretic peptide and a reduction in angiotensin II formation together with a decline in blood pressure and an increase in renal blood flow.…”
Section: Commentmentioning
confidence: 99%
“…The effect of improving renal function after chelation therapy might theoretically relate to removal of essential trace elements, such as zinc and copper, which act as cofactors for enzymes that affect synthesis of vasoactive hormones. 18,19 For example, zinc is a cofactor for neutral metalloendopeptidase, a kidney enzyme of degrading atrial natriuretic peptide, 26 and for angiotensin-converting enzyme. 27 A depletion of zinc might cause an elevation in atrial natriuretic peptide and a reduction in angiotensin II formation together with a decline in blood pressure and an increase in renal blood flow.…”
Section: Commentmentioning
confidence: 99%
“…Recently there has been renewed interest in the role that metalloendopeptidases play in blood pressure control, and thus their potential as therapeutic agents (Carretero & Scicli, 1991). Much of this interest has focussed on endopeptidase E.C.3.4.24:15 (EP 24.15), first identified in soluble fractions of brain homogenates by Orlowski et al (1983).…”
Section: Introductionmentioning
confidence: 99%
“…cFP-AAF-pAB also potentiated the bradykinin-induced vasodepressor response. In preliminary studies, 6 - 7 we found that cFP-AAF-pAB lowers MBP and increases cardiac output, renal blood flow (RBF), and plasma kinins. A recent report 8 states that in vitro cFP-AAF-pAB competitively inhibits purified angiotensin converting enzyme (ACE) with a K, of 0.2 fimo\[L and also inhibits serum ACE activity.…”
mentioning
confidence: 99%